2020
DOI: 10.1111/ene.14451
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐hemispheric transcranial direct current stimulation for upper‐limb hemiparesis in acute stroke: a randomized, double‐blind, sham‐controlled trial

Abstract: Background and purpose Neuromodulation is a promising approach to increasing motor recovery in stroke; however, to date, there is a scarcity of evidence documenting the clinical potential of transcranial direct current stimulation (tDCS) administered in the acute phase of stroke. The present study aims to examine the clinical effects of a treatment involving the application of tDCS in the acute stage post‐stroke. Methods This was a randomized, double‐blind, sham‐controlled trial. A cohort of 32 stroke patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…[27][28][29] The translational potential of our results is supported by a recent study on a small cohort of patients who showed increased rates of upper limb recovery following bihemispheric tDCS over the motor cortex starting 48 to 72 hours after stroke onset. 30 We recently showed that repeated anodal tDCS sessions over the motor cortex promoted motor cortex plasticity and enhanced motor performance in healthy mice. 12 Here we chose bihemispheric stimulation with the anode over the lesioned motor cortex and the cathode over the contralateral side, which should combine the effect of anodal stimulation, increasing excitability and favoring plasticity, and the effect of cathodal stimulation, decreasing the heightened contralesional inhibitory drive that is known to negatively impact motor recovery.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] The translational potential of our results is supported by a recent study on a small cohort of patients who showed increased rates of upper limb recovery following bihemispheric tDCS over the motor cortex starting 48 to 72 hours after stroke onset. 30 We recently showed that repeated anodal tDCS sessions over the motor cortex promoted motor cortex plasticity and enhanced motor performance in healthy mice. 12 Here we chose bihemispheric stimulation with the anode over the lesioned motor cortex and the cathode over the contralateral side, which should combine the effect of anodal stimulation, increasing excitability and favoring plasticity, and the effect of cathodal stimulation, decreasing the heightened contralesional inhibitory drive that is known to negatively impact motor recovery.…”
Section: Discussionmentioning
confidence: 99%
“…We used a 1 × 1 bihemispheric montage using 5 cm square saline saturated sponge (10 mL per sponge) electrodes with an anode over the ipsilesional M1 region for the leg and a cathode on the homologous contralesional side to administer 2 mA tDCS [ 40 ]. We identified a stimulation intensity of 2 mA and a duration of 15 min based on the recommended parameters by the stimulator manufacturing company for the optimal bihemispheric stimulation of the motor area [ 41 , 42 , 43 ]. We identified the optimal electrode placement for the bihemispheric montage by identifying tibialis anterior (TA) hotspots of both the contralesional and ipsilesional hemisphere using a Magstim 200 2 transcranial magnetic stimulator (Magstim Company Ltd., Wales, UK) guided with frameless stereotactic navigation (Brainsight2, Rogue Research, Inc., Montreal, QC, Canada) [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…In keeping with this, bilateral tDCS effects in stroke recovery have been tested in clinical studies showing encouraging results ( Chew et al, 2020 ; Orrù et al, 2020 ). Furthermore, works investigating tDCS capacity to induce changes in cortical electroencephalogram oscillations, suggested that motor recovery might be enhanced by early stimulation that seeks to increase functional connectivity (FC) of motor relays and pathways ( Bolognini et al, 2020 ; bilateral tDCS delivered at 0.57 A/m 2 , 15 min; Vecchio et al, 2018 ; bilateral tDCS delivered at 0.40 A/m 2 , 12 min). Lefebvre et al (2017) showed that one single session of bilateral tDCS (0.28 A/m 2 , 30 min) applied over M1-modulated FC in patients with stroke.…”
Section: Transcranial Direct Current Stimulation and Rewiringmentioning
confidence: 99%